2020
DOI: 10.3390/molecules25204755
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Melanogenic Effects of Korean Red Ginseng Oil in an Ultraviolet B-Induced Hairless Mouse Model

Abstract: A ‘remedy for all’ natural product widely known in the Korean Peninsula is called Panax Ginseng Meyer. Globalization represents a persistent risk to the ozone layer, leading to bountiful amounts of Ultra-Violet B beams (UVB). The variety in human skin hues is ascribed to the characteristic color called Melanin. However, Melanin overproduction due to UVB beams promotes skin staining and tumorigenesis, a process called photo aging, which damages skin quality. To assess the effects of Korean Red Ginseng Oil (KGO)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Moreover, Saba et al exposed HRM-2 hairless mice to UVB radiation and demonstrated the anti-melanogenic effect of the Korean Red Ginseng Oil, possibly by suppressing the expression of MMP-9 and interleukin-1β. Moreover, the topical application of this natural product decreased the melanin production compared with untreated UVB-induced mice [265]. Other natural products have also demonstrated antimelanogenic effects.…”
Section: Radiation-induced Modelmentioning
confidence: 89%
“…Moreover, Saba et al exposed HRM-2 hairless mice to UVB radiation and demonstrated the anti-melanogenic effect of the Korean Red Ginseng Oil, possibly by suppressing the expression of MMP-9 and interleukin-1β. Moreover, the topical application of this natural product decreased the melanin production compared with untreated UVB-induced mice [265]. Other natural products have also demonstrated antimelanogenic effects.…”
Section: Radiation-induced Modelmentioning
confidence: 89%
“…RGO can potentially boost the quality and appearance of skin. Topical application of RGO contributes to the protection skin from environmental hazards such as UV radiation [ 67 , 98 ]. RGO exhibited an inhibitory effect on activity of tyrosinase, which is responsible for melanin production [ 98 ], but was unlikely to inhibit elastase activity [ 58 ].…”
Section: Biological Activities Of Rgo and Their Underlying Mechanismsmentioning
confidence: 99%
“…Topical application of RGO contributes to the protection skin from environmental hazards such as UV radiation [ 67 , 98 ]. RGO exhibited an inhibitory effect on activity of tyrosinase, which is responsible for melanin production [ 98 ], but was unlikely to inhibit elastase activity [ 58 ]. RGO also suppressed melanin production in UVB-treated mouse skin and α-melanocyte stimulating hormone-stimulated B16/F10 cells, possibly through blocking the microphthalmia-associated transcription factor pathway.…”
Section: Biological Activities Of Rgo and Their Underlying Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that red ginseng essential oil has antioxidant and hepatoprotective effects in hydrogen peroxide- (H 2 O 2 -) treated HepG2 cells and carbon tetrachloride- (CCl 4 -) treated mice [ 8 ]. Moreover, a recent study demonstrated the antimelanogenic activities of Korean red ginseng oil (RGO) in a UV-B-induced hairless mouse [ 13 ].…”
Section: Introductionmentioning
confidence: 99%